R&D and Development - Lederman, Daniel; Maloney, William F. (World Bank, Washington, DC, 2014)
Lederman and Maloney trace the evolution of research and development (R&D) expenditures along the development process using a new global panel data set. They show that R&D effort measured as a share of GDP rises with development at an increasing rate. The authors examine how four groups of countries from Latin America, Asia, advanced manufacturing exporters, and advanced natural resource-abundant countries fare relative to the predicted development trajectory. Latin America generally underperforms as do some countries in Asia and Europe, but their striking finding is that some-Finland, Israel, the Republic of Korea, and Taiwan (China)-have radically deviated from the predicted trajectory and displayed impressive R&D takeoffs. The authors ask whether these countries overinvest in R&D but find that the high estimates of the social rates of return probably justify this effort. Moreover, the returns to R&D decline with per capita GDP. The authors attempt to explain why rich countries invest more in R&D than poor countries. They conclude that financial depth, protection of intellectual property rights, government capacity to mobilize resources, and the quality of research institutions are the main reasons why R&D efforts rise with the level of development.